Modified Triphenylamine-Dicyanovinyl-based donor-acceptor dyes with enhanced power conversion efficiency of p-Type dye-sensitized solar cells - Zhu, Linna (2013)
To dye for: Two new dyes are synthesized by structural modifications of one of the best dyes for NiO p-type dye-sensitized solar cells, which is based on a triphenylamine–dicyanovinyl donor–acceptor system. An additional thiophene unit near the anchoring group can greatly retard charge recombination while enhancing the absorption coefficient to significantly improve the photoconversion efficiency by 50 %.